Apakah Welas Diri dan Keberhargaan Diri Kontinjen Berperan dalam Kinerja Akademik pada Remaja? - Felicia; Tiatri, Sri; Iriani R. Dewi, Fransisca (Psyche 165 Journal, 2023)
Academic performance is a learning result that is measured by examination score. A few studies show that Academic Performance is influenced by contingent self-worth. But there is no study that examines if academic performance can be influenced by self-compassion and appearance contingent self-worth. Self-compassion directly influences someone’s ability to evaluate themselves. Appearance contingent self-worth is when someone puts their self-worth in their appearance. This study is conducted to examine the influence of self-compassion and appearance contingent self-worth toward academic performance of junior high school and senior high school students in X school located at North Jakarta. This study uses quantitative methods. Participants were 115 students aged 12 to 18 Junior High School and Senior High School students. Data was collected by questionnaire and examination score. Data collection for variables of academic performance is by math final exam score. Data collection techniques for variables of self-compassion and self-worth contingent on the perception of appearance is a questionnaire whose details are based on self-worth scale and self-compassion scale. The scale used in this study uses a rating scale that is Likert. The result of this study is that self-compassion and appearance contingent self-worth influence academic performance by 7.8%. This research found that self-compassion has positive and significant influence to academic performance. Appearance contingent self-worth has negative and significant influence to academic performance. The next research might include students' perfectionist tendencies and its influences to academic performance.